(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of the studywas to find out the effect of technique training with and without visualpractice on gliding technique and performance of shot putters. To achieve thepurpose of the present study thirty subjects were selected and they weredivided into two groups. Group I underwent technique training with visualpractice of technique and Group II underwent technique training without visualpractice of technique. The data were collected and analysed by using dependent‘t’ test and analysis of covariance (ANCOVA) on technique and performance ofshot put. The results indicated that there was a significant improvement inboth experimental group and significant difference exist between the group Iand II in improvement.